Gauging public perceptions of military and police roles in US domestic pandemic response during COVID-19 - Warren, Evan; Wang, Congruo; Rhodes, Megan; Polatty, David P.; Levine, Adam C. (Frontiers in Public Health, 2025)
IntroductionMilitaries and police forces have been increasingly deployed in response to humanitarian crises and public health emergencies. Existing studies have largely been concentrated around international interventions, overlooking US domestic contexts and the perceptions of those receiving aid.MethodsIn recognition of these gaps, this research involved a survey of 1,500 Americans to understand opinions toward the utilization of the US military and local law enforcement as COVID-19 domestic pandemic responders at an unprecedented scale.ResultsA majority were complimentary of and comfortable with these armed actors' role in the response and supportive of involvement in future crises, with the military regarded more favorably than police. Trust in civilians, the military, and police is found to be role-based; favorability was inherently tied to the nature of services provided, whether healthcare, logistics, or enforcement-related. Perceptions were also strongly linked to one's vaccination status, political party affiliation, ideology, age, and gender. Underlying trust in civilian providers was evident, but often did not preclude one from favorable views of the military and law enforcement.ConclusionUltimately, these results have implications on domestic policy in future national crisis scenarios and highlight the need for further research exploring if sentiment holds steady beyond the realm of public health and pandemics.